Masculine honor beliefs: Measurement and correlates. (May 2016) - Saucier, Donald A.; Stanford, Amanda J.; Miller, Stuart S.; Martens, Amanda L.; Miller, Alyssa K.; Jones, Tucker L.; McManus, Jessica L.; Burns, Mason D.
Abstract: Masculine honor, particularly as defined by the Southern culture of honor, centers on the belief that aggression is sometimes justifiable and necessary, such as in response to insult or threat. While masculine honor has been examined in terms of cultural differences, it has been less often examined in terms of individual differences. We developed a measure of masculine honor beliefs (MHBS) inspired by research on the Southern culture of honor. Four studies showed that the MHBS demonstrated internal consistency, test–retest reliability, convergent validity with measures of trait aggression and sexism, discriminant validity from measures of social desirability, conservatism and self-esteem, and predictive and incremental validity in predicting reactions to honor-related provocation above and beyond participants' sex and other measures of honor beliefs. The MHBS allows masculine honor beliefs to be examined as an important factor in understanding men's motivations for aggressive behavior, particularly in response to provocation. Highlights: The Southern culture of honor centers on the belief that male aggression is sometimes justifiable and necessary. We developed a measure of masculine honor beliefs (MHBS) inspired by research on the Southern culture of honor. The MHBS can be used to assess both men's and women's beliefs about men's behavior. The MHBS assesses the various components that comprise masculine honor beliefs more comprehensively than previous measures. The MHBS was found to be related to endorsement of aggressive behavior, particularly in response to provocation.